Voice conversion with parallel/non-parallel data and synthetic speech detection - Tian, Xiaohai (2019)
The objective of voice conversion techniques is to convert a source speaker's voice so that it sounds like that of a target speaker. Voice conversion belongs to a popular area of personalized speech generation. On one hand, it can be applied to solve problems, e.g. emotion conversion, improving the intelligibility of speech, or change whisper/murmur into speech. On the other hand, voice conversion also presents a threat to Automatic Speaker Verification (ASV) systems. Synthetic speech detection is a technique to discriminate between live and synthetic speech. In this sense, it provides a feasible way to improve robustness and protect ASV systems. This thesis focuses on the following two aspects: improving performance in voice conversion and studying countermeasures for synthetic speech detection.